The Very Hungry Caterpillars Peekaboo Valentine - Carle, Eric ([New York, N.Y.] : World of Eric Carle, an imprint of Penguin Random House LLC, 2024)
"See if you can spot The Very Hungry Caterpillar among a box of chocolates, a decorated valentine, and more!"-- Provided by publisher.
Ages 1-3.
Keywords: Caterpillars -- Juvenile fiction; Valentines Day -- Juvenile fiction; Caterpillars -- Fiction; Valentines Day -- Fiction; Stories in rhyme; Board books; Picture books